An Analysis of Written Commentary Technique on Students’ Writing Given by Teachers - Yuniko, Fajrilhuda; Ilahi, Rahma Kurnia (International Journal of Multidisciplinary Approach Research and Science, 2024)
This research was based on a phenomenon that the students’ writing ability was still low. It was assumed that there were two main factors influencing the students’ writing. One of them was about facilitating the students with appropriate written feedbacks. In line with that, this research was a kind of descriptive study, which was aimed at finding a deep description of the implementation of written feedback at MAN Koto Baru Padang Panjang. Participants of the research were all English teachers there. Furthermore, the data were collected by using two instruments, documents and interview. There were two findings of the research. First, almost all of the written feedback items were provided to help students working on their grammatical mistakes or forms of the writing, it was proven by the percentage that 99.66% of the written feedback items were focused on forms whereas only 0.34% of the written feedback items were focused on contents. Second, the technique used in giving the written feedback was written commentary. This technique was used due to its effectiveness in helping the students’ writing. In short, giving written feedback through the written commentary technique is really worth for the development of students’ writing, especially for non-native of English.